2022
DOI: 10.1080/22221751.2022.2046446
|View full text |Cite
|
Sign up to set email alerts
|

The Protection of Naturally Acquired Antibodies Against Subsequent SARS-CoV-2 Infection: A Systematic Review and Meta-Analysis

Abstract: The specific antibodies induced by SARS-CoV-2 infection may provide protection against a subsequent infection. However, the efficacy and duration of protection provided by naturally acquired immunity against subsequent SARS-CoV-2 infection remain controversial. We systematically searched for the literature describing COVID-19 reinfection published before 07 February 2022. The outcomes were the pooled incidence rate ratio (IRR) for estimating the risk of subsequent infection. The Newcastle–Ottawa Scale (NOS) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 65 publications
1
16
3
Order By: Relevance
“…This was the period where testing capacity was severely constrained and there was greater bias towards testing individuals with risk factors for severe disease. Overall, our finding is broadly in line with studies included in a systematic review examining the issue of relative anti-N seropositivity protection (21).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This was the period where testing capacity was severely constrained and there was greater bias towards testing individuals with risk factors for severe disease. Overall, our finding is broadly in line with studies included in a systematic review examining the issue of relative anti-N seropositivity protection (21).…”
Section: Discussionsupporting
confidence: 89%
“…While the fourth wave saw a sharp increase in SARS-CoV-2 cases, this did not result in a concomitant increase in related mortality (see line graph in Figure 1). Analyses from our setting have found that the Omicron variant was associated with less severe disease when compared to the Delta variant (20,21), but the low case ascertainment rates in this study complicates this interpretation (22).…”
Section: Discussionmentioning
confidence: 59%
“…Antibodies to the SARS-CoV-2 spike and nucleocapsid proteins are generated in over 90% of individuals with symptomatic infection and persist for months (9)(10)(11)(12)(13)(14). Multiple studies following up individuals with SARS-CoV-2 infection have described protection from SARS-CoV-2 following natural infection in individuals with detectable antibody levels: protection from subsequent symptomatic infection with SARS-CoV-2 was estimated at about 85% protection in two overlapping meta-analyses of 19 studies performed in the general population, health care workers, college students, and residents in long-term care facilities (15,16). In some studies, quantitative antibody levels were recorded, and increased protection in individuals with higher antibody levels was observed (10,17).…”
mentioning
confidence: 99%
“…The NOS scale scores articles according to 8 questions in 3 domains, with a total score of 9. A study with a score of 0–3 was rated as low quality; a study with a 4–6 score was considered as moderate quality; and a study with a 7–9 score was graded as high quality ( 17 ). In contrast, the risk of bias in the included cross-sectional studies was assessed using the Joana Brigg’s Institute (JBI) critical appraisal checklist, with a total score of nine.…”
Section: Methodsmentioning
confidence: 99%